Case Report: Chronic Urticaria Elimination through Ayurvedic Management. - Anaghashree , S; Chaitra , H; Ranjeetha, K (International Research Journal of Ayurveda & Yoga, 2023)
A widespread concern in society nowadays is urticaria. Hives, or urticaria, are typically brought on by an allergic reaction. Due to symptoms being comparable, sheetapitta is considered to be a related ailment in ayurveda. The terms sheeta and pitta combine to form the word sheetapitta. The illness develops as a result of pitta dosha’s dominance over the cold. When exposed to cold breeze pitta dosha mix with worsened kapha and vata doshas. These disperse throughout the body and cause rashes to appear on the skin’s surface. A 55-year-old female patient has been complaining of reddish, raised, circular rashes all over her body since 5 years. These rashes were getting worsened after her anti-allergic medications were missed, hence, she had continued the medications regularly from past 5 years. Due to which she had increased drowsiness making her disabled to do her day course. This condition was diagnosed as sheetapitta and was further treated with shamana aushadis both internally and externally along with strict monitoring of pathya.